Diseño de bombeo electrosumergible para pozos de baja producción y/o bajas presiones de fondo - Loor Alvarado, Karen Arelis (2010)
In this graduation last paper show the best design of Electro Sumergible Pump for a well of low production and low pressure background, the aim being to determine the best option for increasing production and equipment life (run life), plus lower maintenance costs by changing the selected well artificial lift system, hydraulic to electrosumergible, then selected some ideal applications for the ESP (Electrical Submersible Pump) as: ESP above of the shooting, ESP belove of the shooting, ESP with refrigeration jacket above of the shooting, ESP with refrigeration jacket belove of the shooting. Additionally, details the use and benefit of a recirculating pump, compared with a BES with refrigeration jacket. The new recirculating pump was implemented in Ecuador in 2010. In Argentina has been successful.